Structural insight into DNA recognition by bacterial transcriptional regulators of the SorC/DeoR family - Šoltysová, Markéta; Sieglová, Irena; Fábry, Milan; Brynda, Jiří; Škerlová, Jana; Řezáčová, Pavlína (Acta crystallographica. Section D, Structural biology, 2021)
The SorC/DeoR family is a large family of bacterial transcription regulators that are involved in the control of carbohydrate metabolism and quorum sensing. To understand the structural basis of DNA recognition, structural studies of two functionally characterized SorC/DeoR family members from Bacillus subtilis were performed: the deoxyribonucleoside regulator bsDeoR and the central glycolytic genes regulator bsCggR. Each selected protein represents one of the subgroups that are recognized within the family. Crystal structures were determined of the N-terminal DNA-binding domains of bsDeoR and bsCggR in complex with DNA duplexes representing the minimal operator sequence at resolutions of 2.3 and 2.1 Å, respectively. While bsDeoRDBD contains a homeodomain-like HTH-type domain, bsCggRDBD contains a winged helix-turn-helix-type motif. Both proteins form C2-symmetric dimers that recognize two consecutive major grooves, and the protein-DNA interactions have been analyzed in detail. The crystal structures were used to model the interactions of the proteins with the full DNA operators, and a common mode of DNA recognition is proposed that is most likely to be shared by other members of the SorC/DeoR family.
Keywords: SorC/DeoR family; molekulární modely; konformace proteinů; Binding Sites; deoxyribonucleoside regulator bsDeoR; DNA vazebné proteiny; Bacillus subtilis; bakteriální proteiny; Protein Binding; Models, Molecular; Bacterial Proteins; DNA-Binding Proteins; Crystallography, X-Ray; gene regulator bsCggR; krystalografie rentgenová; protein–DNA complexes; carbohydrate catabolism; Protein Conformation; transcription repressors; DNA; vazebná místa; vazba proteinů